Advanced space- and time-resolved techniques for photocatalyst studies. Issue 7 (3rd January 2020) - Gao, Yuying; Nie, Wei; Wang, Xiuli; Fan, Fengtao; Li, Can
Abstract : Nanoparticle photocatalysts present the obvious characteristic of heterogeneity in structure, energy, and function at spatial and temporal scales. Abstract : Nanoparticle photocatalysts present the obvious characteristic of heterogeneity in structure, energy, and function at spatial and temporal scales. Understanding the nature of spatial variations and reaction dynamics in photosynthetic solar energy conversion systems at the single particle level is of crucial importance to clarify the underlying mechanism of photocatalytic reactions. In this review, we focus on advanced characterization tools employed to reveal the physical and chemical properties of photocatalysts in space and time. We highlight the recent significant progress to elucidate the microscopic mechanisms of photogenerated charge generation, transfer and recombination and surface reaction kinetics. We also discuss the primary advantages and limitations of these characterization approaches and the development of powerful tools in photocatalysis in the future.